THE INFLUENCE OF TAXES, COMPANY SIZE, AND FOREIGN OWNERSHIP ON THE DECISION OF COMPANIES TO CONSIDER TRANSFER PRICING ON MANUFACTURING COMPANIES LISTED IN THE IDX - Nani Rohaeni; Dina Khairuna Siregar; Iyah Hamdiyah Safitri (Yayasan Education and Social Center, 2021)
Transfer pricing has long been a classic issue in the taxation field. From the government side, transfer pricing is supposed to reduce and eliminate the potential for state tax revenue, because multinational companies shift the tax obligations of countries that have high tax rates (high tax countries) to countries with low tax rates (low tax countries). The purpose of this study is to fund out partially the effect of tax, company size, and foreign ownership on company decisions do transfer pricing. And to determine the effect of taxes, size foreign ownership in the company and simultaneously against the decision of the company do transfer pricing on manufacturing companies listed in Indonesia Stock Exchange period 2015-2019. The method used in this study is an associative method with a quantitative approach. The research population totals 183 companies with a sample of 11 companies, the financial report data attached 55 data using purposive sampling technique, the research was conducted at manufacturing companies in the Indonesia Stock Exchange period 2015-2019. The conclusion of the research is based on the above calculation partially, the results obtained by the tax and foreign ownership variable affect the company's decision to transfer pricing, while the variable company size does not affect the company's decision to transfer pricing. Simultaneously, the tax variables, company size, and foreign ownership affects the company's decision to transfer pricing to manufacturing companies in the Indonesia Stock Exchange period 2015-2019.